The Impact of TQM Tools and Organisation Performance In Malaysia Small And Medium Enterprise (SMEs): A Survey Result - Ahmad, Md Fauzi; Siew Yin, Jessica Chan; Muhd Nor, Nik Hisyamudin; Shiau Wei, Chan; Abdul Hamid, Norhadilah; Ahmad, Ahmad Nur Aizat; Abdul Rahman, Nor Aida; Mohd Nawi, Mohd Nasrun (International Journal of Supply Chain Management, 2018)
Total Quality Management (TQM) is an important management tool for continuous improvement in an organization for enhancing their performance. TQM tools are very essential in supporting TQM activities. However, small and medium enterprises (SMEs) have inadequate resources and awareness of motivation for implementing TQM tools in their companies. Hence, the purpose of this study is to identify the extent level of TQM tools and to examine the relationship between TQM tools and organisational performance. Hypotheses have been developed by identifying twenty TQM tools which considered vital in TQM implementation. 400 questionnaires have been distributed through random sampling in final study. Finally, 80 questionnaires were received or 25.0% response rate for final study. The study result shows that the extent level in TQM tools is in high and moderate level. Furthermore, there is a significant relationship between TQM tools and organisational performance in SMEs. However, the relationships are in moderate and low level. The study is important for SMEs to gain insight on the effect of TQM practices towards TQM tools in organizational performance and identify the most important tools and techniques for their companies in future implementation